Differences in Creative Thinking Abilities of High School Students from Village and City - Bowo Sugiharto; Elma Rosalia Malinda; Ihrom Rosyadi; Maulidya Dwi Anggini; Nur Rochmah Candra Padmi; Rahmat Evendi (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to distinguish the creative thinking ability of high school students in Biology subject. This research method uses a quantitative approach and the type of research is descriptive. The population that used was all students of XII MIPA of high school in rural and urban areas by taking a sample of 30 students per each school. The instrument that used was a test of creative thinking ability on chapter ‘Animalia’ in the form of 40 multiple choice questions that contained indicators of creative thinking ability. This research used descriptive qualitative analysis with data collection techniques using cognitive observation techniques. The results showed that there was a difference between the student’s ability to think creatively in rural school (village) and urban school (city).